Takhrij and Syarah Hadith about Chemistry : The Study of the Uniqueness of Iron in a Scientific Perspective - Fathimah Az-Zahra; Resti Widianengsih; Tety Sudiarti; Didin Komarudin; Etin Etin (UIN Sunan Gunung Djati Bandung, 2021)
This research discusses the hadith about the privileges of iron. This research method is qualitative through literature study with the approach of takhrij and sharah hadith and chemical analysis. The result and discussion of this research is that iron was popular during the Rosulloh Saw era, because of its special iron content that other metals do not have, although iron can rust and corrosive behind it. The conclusion of this research is takhrij and syarah hadith of the Prophet. about the specialty of iron by chemical analysis has experimental opportunities as well as various benefits for living things.